PENGELOLAAN FASILITAS DI RE CAFFE PLATINUM SEBAGAI SALAH SATU DESTINASI WISATA KULINER DI PEKANBARU - Maharani, Suci; ,, Etika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to find out the Management of Main Facilities at Re Caffe Platinum as One of the Culinary Tourism Destinations in Pekanbaru, and to find out the obstacles faced by Re Caffe Platinum in managing the main facilities. In this study, the method used by the author is a qualitative method with data collection techniques using observation, interviews, and documentation. Key informants in this study were the vice direction, manager, members, and visitors of Re Caffe Platinum. Based on the results of the study, it can be concluded that facility management aims to ensure that facilities and infrastructure can function optimally, facility management at Re Caffe Platinum has five stages, namely planning, organizing, directing, coordinating, and controlling. There are several obstacles that occur in the stages of managing the main facilities, but Re Caffe Platinum can still overcome them so that the management of Re Caffe Platinum facilities continues to run well. It's just that the main facilities of the outdoor dine-in area behind still need improvement. Keywords: Management, Facilities, Re Caffe Platinum